Supply Chain Complexity and Its Impact on Knowledge Transfer: Incorporating Sustainable Supply Chain Practices in Food Supply Chain Networks - Hareer Fatima Ahmed; Amin Hosseinian-Far; Dilshad Sarwar; Rasoul Khandan (Logistics, 2024)
Background: The dynamics of supply chain networks have changed due to increasing complexities. Global expansions and knowledge transfer in supply chain networks bring efficiency and effectiveness to companies. However, the probability of supply chain complexity has also been seen increasing. The barriers to sustainable supply chain networks need to be tackled in an effective manner as they impact business operations. Therefore, it is essential to eliminate and reduce the supply chain complexities, as it will facilitate the process of knowledge transfer and increase the implementation of sustainable practises in supply chain networks. In the previous research, four supply chain complexity drivers were identified. Previous research identified four supply chain complexity drivers by conducting a systematic review. This study investigates which of the four complexity drivers impacts knowledge transfer in the context of the food supply chain sector. Methods: In this research, knowledge transfer is therefore examined from the perspective of sustainable food supply chains. Thirty exploratory qualitative interviews were conducted in this study and analysed using Nvivo (v12) software. This study utilised thematic analysis techniques for the evaluation of the interviews to gather results. Results: The results illustrated six main factors classified under broad categories: integration of Knowledge Transfer, incorporation of technological advancements in supply chain networks, supply chain complexity solutions, supply chain complexity drivers, sustainable supply chain networks, and capability to reduce supply chain complexity. The findings of this study highlight that process complexity significantly influences the process of knowledge transfer in food supply chain networks. The research findings contribute to both academic and practical domains. This study contributes to the aggregation of supply chain complexity and its impact on Knowledge Transfer. Additionally, the findings support supply chain networks, which strive to achieve efficient Knowledge Transfer to attain sustainable value in business operations. Conclusion: This study has proven that robust knowledge transfer reduces supply chain complexity as it makes supply chain systems more resilient and well-coordinated in many potential ways.